1995
DOI: 10.1002/app.1995.070571312
|View full text |Cite
|
Sign up to set email alerts
|

Physical principles of using polyelectrolyte hydrogels for purifying and enrichment technologies

Abstract: SYNOPSISThe main physical regularities which allow one to use a strongly charged hydrogel in purifying and/or enrichment technologies are analyzed. The proposed cyclic method is based on the two known phenomena-the salt concentration redistribution in the presence of the polyelectrolyte hydrogel and the reversible gel contraction under electric current. It is shown that in order to obtain high degrees of purification and/or concentration the salt concentration must be lower than that of the polymer. Under thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…Reversible collapse of polyelectrolyte hydrogels and its applications are continuously studying in current literature. Thus, on this base biomimetic devices [1,2], ecological technologies [3], etc may be developed. Y.Osada et al reported a number of experiments demonstrating wide possibilities of application of hydrogels for transformation of energy from the one form to another [4].…”
Section: Introductionmentioning
confidence: 99%
“…Reversible collapse of polyelectrolyte hydrogels and its applications are continuously studying in current literature. Thus, on this base biomimetic devices [1,2], ecological technologies [3], etc may be developed. Y.Osada et al reported a number of experiments demonstrating wide possibilities of application of hydrogels for transformation of energy from the one form to another [4].…”
Section: Introductionmentioning
confidence: 99%
“…These have a number of potential applications in the pharmaceutical, food, and environmental industries. [4][5][6] There has also been considerable recent activity in the incorporation of such polyelectrolytes and hydrogels into conducting polymers based on polypyrrole and polyaniline, to generate composites that combine favorable structural and processability features with good conductivity. [7][8][9][10] Optically active synthetic polymers, including gels and chiral conducting polymers are also of current interest because of their chiral recognition properties and their potential applications for asymmetric synthesis, as chiral stationary phases in HPLC and as chiral membranes for the separation of mixtures of enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…Such monomers have also been used to form hydrogels with cross-linked, interpenetrated networks. These have a number of potential applications in the pharmaceutical, food, and environmental industries. …”
Section: Introductionmentioning
confidence: 99%
“…Наиболее экологически приемлемыми являются методики опреснения, основанные на использовании цикла сжатия -набухания гидрогелей. В настоящее время известен целый ряд разновидностей такого рода методик опреснения [6,7], причем теоретическое описание любой из них укладывается в концепцию, восходящую к [1].…”
unclassified
“…Однако их практическое использование затруднено необходимостью создавать ионные токи (например, вызывающие коллапс гидрогелей) при помощи сторонних сил (электрический ток [6] или механическое воздействие [7]). В то же время существует возможность реализовать ионный ток непосредственно при помощи протекания раствора через гель (Рис.1).…”
unclassified